2020
DOI: 10.33233/fb.v21i1.2926
|View full text |Cite
|
Sign up to set email alerts
|

Condições de vida e saúde de idosos funcionários de uma faculdade particular

Abstract: Introdução: Há um grande percentual de idosos inseridos no mercado de trabalho e essa estimativa tende a crescer devido ao aumento significativo dessa população, acreditando que, em 2020, 15% da população será idosa, e 13% estará inserida no mercado de trabalho. Objetivo: Avaliar as condições de vida e saúde em idosos que exerçam atividade profissional. Métodos: Estudo transversal, quantitativo, censitário, descritivo, realizado em uma Instituição de Ensino Superior com idosos de ambos os sexos, funcionários d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Taken together, our findings are in accordance with other studies that show a low purchasing power is one of the characteristics of the older population in Brazil and social benefits are the main income source (46,47,51). This national scenario requires the state to formulate and implement public policies to assist this population, especially associated with social security.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Taken together, our findings are in accordance with other studies that show a low purchasing power is one of the characteristics of the older population in Brazil and social benefits are the main income source (46,47,51). This national scenario requires the state to formulate and implement public policies to assist this population, especially associated with social security.…”
Section: Discussionsupporting
confidence: 91%
“…In general, the low income of Brazilians individuals aged 80 and over has been described in some studies (45,46), however, the discrepancies observed in the incomes could be explained by the region in which the studies were conducted. The studies that described long-lived people with higher income levels (2 to 3 minimum-wages) were carried out in the municipality of Marilia, a municipality in the state of São Paulo (47), in the south of state of Minas Gerais (48) and the Brazilian Federal District (49), while the studies that observed an average income of 1 minimum wage were conducted in the city of Recife, state of Pernambuco (50). The participants of the present study live in São Paulo, one of the richest states in the federation and has better health services that can contribute to better living conditions when compared to other regions of the country.…”
Section: Discussionmentioning
confidence: 99%